High commitment work system and innovative work behavior: The mediating role of knowledge sharing - Fiza Ahmed; Atif Hassan; Malik Umer Ayub; Richard J. Klimoski (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
In this modern and competitive era, organizations for their endurance and success rely on the innovative ideas. For today's managers it becomes imperative to look for those ways and means through which they could innovate and this research is very much highlighting the said aspect. This study empirically examines and explores the impact of high commitment work system on innovative work behavior and addresses the role of knowledge sharing as a mediator. Basically, it provides a mechanism through which high commitment work system fosters innovative work behavior in telecommunication sector companies of Pakistan. Using the findings of this research, telecommunication companies, particularly mobile network companies can transform and bring novelty in their services to proliferate in a competitive market. All the established relationships are theoretically explained, empirically tested and supported through literature review. Results revealed that all three variables of the study exhibit positive relationship. All four established hypotheses are accepted and the relationship between high commitment work system and innovative work behavior partially mediated by knowledge sharing behavior.
Keywords: 330; high commitment work system; knowledge sharing; innovative work behavior